Antecedents and consequences of silent treatment in close adult relationships: a systematic review - Dubey, Avni; Kumar, Ravinder; Srivastava, Akriti; Tamarana, Rameshbabu; Yadav, Anupam; Sharma, Vishal; Saini, Satvinder Singh (Frontiers in Psychology, 2026)
BackgroundThe silent treatment, characterized by deliberate communication avoidance, is a common form of social exclusion that significantly impacts close adult relationships. Although, often regarded as a minor issue, its persistent use can lead to serious emotional and psychological consequences.MethodsThis systematic review aimed to consolidate research findings to identify the antecedents and consequences of the silent treatment in interpersonal relationships. Following PRISMA (2020) guidelines, 15 peer reviewed articles were analyzed, and sourced from databases and search engines including PubMed, Google Scholar, Science Direct, and Web of Science.ResultsThe antecedents identified through these studies were emotional regulation, personality traits, manipulation tactics, cognitive processes, relational contexts and to some extent gender. The consequences identified for both givers and receivers of the silent treatment were decreased overall psychological health with long-term emotional distress and poor relationship satisfaction.ConclusionThese findings emphasize the need for improved communication strategies and interventions to address the detrimental effects of silent treatment in various relational contexts.